Pengembangan Modul Ajar Mata Pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) Kelas IV Kurikulum Merdeka Materi Indonesiaku Kaya Budaya di SDN 24 Pontianak Timur - Kharina Murti; Hery Kresnadi; Siti Halidjah (Departement of Mathematics Education, 2023)
This research aims to develop teaching module products for the Natural Sciences subject, My Indonesia Rich Culture Material, which are feasible and practical to use. This study uses a mixed approach (mix method) with the Research and Development (R&D) method. The data analysis technique uses the Research and Development (R&D) model adapting the 4D development model (four D models) developed by Thiagarajan which consists of 4 stages, namely define, design, development, and dissemination. . The data sources in this study were the validation results of the questionnaire validating the completeness of the teaching module components and the material aspects of the teaching modules from two validators and the results of the practicality of the teaching modules from the homeroom teachers of class IVA and IVB SDN 24 Pontianak Timur. The level of feasibility of the teaching module for the Science Science subject, My Indonesia Rich Culture Material, is based on the results of the validator team's assessment. The results showed that the feasibility of the teaching modules was stated to be